Guía Etnobotánica de la Flora de Páramo del Iliniza Sur de las Comunidades aledañas a la Parroquia Toacaso, Cantón Latacunga, Provincia de Cotopaxi - Parreño Zapata, María Belén (2019)
The present investigation was carried out due to the lack of information on the uses of the páramos plants that are affected by the agricultural activities of the surrounding communities; Therefore, it was necessary to carry out a study to know the species of flora and their respective uses, obtaining as a result an ethnobotanical guide to the páramo flora, integrating the utility and benefits given by the communities of: Cotopilalo, Rasuyacu Corazon de Jesús and Samaná, located on the slopes of Iliniza Sur belonging to the parish of Toacaso. Randomized tours, selection of sites of interest were made, and in turn key actors were determined who would provide relevant and important information for the situational diagnosis, in the development of the register of cultural processes the INPC data sheets related to knowledge and use were applied related to nature and the universe resulting in 19 ancestral knowledge in relation to the usefulness of both medicinal plants. Food and Rituals. On the other hand, in the botanical aspect the selection was collected, pressed, dried, assembled and taxonomic identification of 57 plant species. With the final listings of plants and cultural processes, sensitivity to change was evaluated, resulting in 83% having a lower sensitivity, and that 17% represents a high sensitivity since much knowledge is transmitted by adults and senior citizens On the other hand, the conservation status represents that 75% of the collected plants are in a state of not evaluated, while 7 plants are in a state of concern less than 12% and finally there are eight plants that are not It has been evaluated equivalent to 14%. The methodology applied in the project was a field investigation, where it began with the selection of study sites, key actors, the registration of cultural processes and the selection, collection and taxonomic identification of plants, and finally the bibliographic research for the validity of the information obtained both in the botanical and cultural field. Finally, in the design of the ethnobotanical guide, cultural processes and their taxonomic identification of them will be collected and reflected.